ГДЗ по алгебре 9 класс Е.П. Кузнецова глава 1 / 79

показать содержание

1.79. Изобразите график квадратичной функции и укажите его ось симметрии: 1)у = (х-4)2 + 3; 2) у = (5 - х)2 + 2; 3) у = -(х + 2)2- 1; 4) у = -(х - З)2 - 4; 5) у = Зх2 - 9х; 6) у = -2х2 + 8х; 7) у = (х + 3)(х - 2); 8) у = (х + 3)(х + 1); 9) у = 2х2 + х - 6; 10) у = 2х2 - х - 5.

учебник / глава 1 / 79
1.79.	Изобразите график квадратичной функции и укажите его ось симметрии:
1)у = (х-4)2 + 3;	
2) у = (5 - х)2 + 2;
3) у = -(х + 2)2- 1;	
4) у = -(х - З)2 - 4;
5) у = Зх2 - 9х;	
6) у = -2х2 + 8х;
7) у = (х + 3)(х - 2);	
8) у = (х + 3)(х + 1);
9) у = 2х2 + х - 6;	
10) у = 2х2 - х - 5.
решебник 1 / глава 1 / 79
1.79.	Изобразите график квадратичной функции и укажите его ось симметрии:
1)у = (х-4)2 + 3;	
2) у = (5 - х)2 + 2;
3) у = -(х + 2)2- 1;	
4) у = -(х - З)2 - 4;
5) у = Зх2 - 9х;	
6) у = -2х2 + 8х;
7) у = (х + 3)(х - 2);	
8) у = (х + 3)(х + 1);
9) у = 2х2 + х - 6;	
10) у = 2х2 - х - 5.
решебник №2 / глава 1 / 79
1.79.	Изобразите график квадратичной функции и укажите его ось симметрии:
1)у = (х-4)2 + 3;	
2) у = (5 - х)2 + 2;
3) у = -(х + 2)2- 1;	
4) у = -(х - З)2 - 4;
5) у = Зх2 - 9х;	
6) у = -2х2 + 8х;
7) у = (х + 3)(х - 2);	
8) у = (х + 3)(х + 1);
9) у = 2х2 + х - 6;	
10) у = 2х2 - х - 5. 1.79.	Изобразите график квадратичной функции и укажите его ось симметрии:
1)у = (х-4)2 + 3;	
2) у = (5 - х)2 + 2;
3) у = -(х + 2)2- 1;	
4) у = -(х - З)2 - 4;
5) у = Зх2 - 9х;	
6) у = -2х2 + 8х;
7) у = (х + 3)(х - 2);	
8) у = (х + 3)(х + 1);
9) у = 2х2 + х - 6;	
10) у = 2х2 - х - 5. 1.79.	Изобразите график квадратичной функции и укажите его ось симметрии:
1)у = (х-4)2 + 3;	
2) у = (5 - х)2 + 2;
3) у = -(х + 2)2- 1;	
4) у = -(х - З)2 - 4;
5) у = Зх2 - 9х;	
6) у = -2х2 + 8х;
7) у = (х + 3)(х - 2);	
8) у = (х + 3)(х + 1);
9) у = 2х2 + х - 6;	
10) у = 2х2 - х - 5. 1.79.	Изобразите график квадратичной функции и укажите его ось симметрии:
1)у = (х-4)2 + 3;	
2) у = (5 - х)2 + 2;
3) у = -(х + 2)2- 1;	
4) у = -(х - З)2 - 4;
5) у = Зх2 - 9х;	
6) у = -2х2 + 8х;
7) у = (х + 3)(х - 2);	
8) у = (х + 3)(х + 1);
9) у = 2х2 + х - 6;	
10) у = 2х2 - х - 5.

популярные учебники